2010
DOI: 10.1680/geng.2010.163.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Low-volume-loss tunnelling for London ring main extension

Abstract: The Thames Water ring main extension is a 4·5 km long tunnel from Stoke Newington, in the London borough of Hackney, to New River Head in Finsbury, in the London borough of Islington. The 2·85 m i.d. tunnel was excavated by an earth pressure balance tunnel-boring machine (TBM) at depths between 40 and 60 m below the surface. Surface settlements along the route were measured by precise levelling, and were found to be small. It was therefore even more important to measure these settlements as accurately as possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
3
0
8
Order By: Relevance
“…It is worth noting that Jones (2010) showed that the Mair et al (1993) expression can overestimate the value of K for deep tunnels. Based on field data measurements, Jones proposed a logarithmic formula for the prediction of K which depends on the height above the tunnel z t À z rather than the relative depth z/z t .…”
Section: Empirical Methodsmentioning
confidence: 99%
“…It is worth noting that Jones (2010) showed that the Mair et al (1993) expression can overestimate the value of K for deep tunnels. Based on field data measurements, Jones proposed a logarithmic formula for the prediction of K which depends on the height above the tunnel z t À z rather than the relative depth z/z t .…”
Section: Empirical Methodsmentioning
confidence: 99%
“…en, concrete segment lining is installed just rear of the shield skin plate as a permanent ground supporting structure, where simultaneous backfilling of pressurized grout is also conducted at the annulus gap around the segment lining to restrict excessive radial contraction of the excavated ground. According to the field observations in the literatures [2][3][4], ground settlement during shield TBM tunnelling develops in the following steps in accordance with the abovementioned ground supporting mechanisms: (1) before and during tunnel face excavation, (2) during passage of the shield skin plate, and (3) after installation of segmental lining and backfill grouting.…”
Section: Introductionmentioning
confidence: 91%
“…Finally in this special issue Jones (2010) presents predictions for, and actual sub surface movement measurements of, underground structures adjacent to an extension to the Thames Water Ring main tunnel in North London. This case history indicated that the tunnelling settlement trough width parameter K did not vary with depth as predicted, leading to a new relationship being proposed…”
Section: Editorialmentioning
confidence: 99%